PREVALENCE AND RISK FACTORS OF OBESITY IN PRIMARY SCHOOL IN URBAN AND RURAL AREAS - Ratna Dewi, Made; Sidiartha, I Gusti Lanang (Medicina; Vol 44 No 1 (2013): Januari 2013)
Normal 0 false false false IN X-NONE X-NONE Obesity has become a continous increasing global health problem. Obesity can happen in adult population and also on children as well as teenagers. There are several factors that influence the occurrence of obesity. The aim of this study is to determine the prevalence and risk factors for obesity in primary school children in urban and rural areas. A cross sectional study was conducted with a total sample of 241 pupils in several elementary schools . Anthropometric status determine using body mass index for age and obesity stated if measurement exceed ?95 th percentile based on CDC 2000. Analysis data perform with the Pearson Chi-square, Fisher's Exact Test, and logistic regression. A P value of <0.05 was considered significant. This study showed the prevalence of obesity was 15%. The prevalence of obesity in urban areas was 21% and rural areas was 5%. The result showed risk of obesity multiplied by 3.8 times in urban children as they had a habit of "snacking" had risk of suffering obesity by 3.4 times (95% CI 1.2 to 9.0) . Children who had habit of having fast food more than 2 times per week had the more risk of obesity by 5 times (95% CI 1.9 to 13.5) . Mothers education in urban areas as a protective factor. Conclusion of this study show that the prevalence of obesity in urban areas is 21% and 5% in rural areas. “Snacking” habit and eating fast food more than 2 times per week increase the risk of obesity in urban areas, while in rural areas no risk factors consider significant for obesity. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: obesity, children, prevalence